The red house - Abbott, Tony, 1952- (Abbott, Tony, 1952- Haunting of Derek Stone, 2009)
The Legion is back in full force, and they're heading for Amaranthia, the mysterious, long-abandoned house on the Red River which holds a clue that could completely change the war between the living and the dead. Derek doesn't even know what he's looking for, but he knows he has to find it first.